A RETROSPECTIVE STUDY OF SCROTAL PAIN FOLLOWING VARICOCELECTOMY, CAUSES AND MANAGEMENT (Eureka Journal of Health Sciences & Medical Innovation, 2026)
An average of 8–15% of inactive men will develop varicocele, a common urological ailment. The incidence is greater in male patients suffering from primary or secondary infertility; in fact, between 35 and 80% of varicocele cases occur in this group. Clinical manifestations of a varicocele typically include an asymptomatic mass that looks like a "bag of worms", infertility, persistent pain in the scrotum, and a lump. When other treatments for varicocele fail, the patient may be referred for surgery. Regrettably, some individuals may experience persistent scrotal pain due to nutcracker syndrome, referred pain, neuralgia, ureteral lesions, varicocele recurrence, hydrocele, or neuralgia. Doctors should manage scrotal pain following surgery based on the patient's symptoms, which may include these concerns. Taking into account a multitude of variables can better predict the success rate of varicocele surgery. Before deciding whether surgery is necessary and what course of action is optimal, clinicians should contemplate these factors. If patients follow these steps, surgery is more likely to be successful and complications like postoperative scrotal pain are less likely to occur. Techniques and results Between July 2021 and July 2023, 212 patients were diagnosed with varicocele. Surgeons from the urology department at Baquba Teaching Hospital conducted the varicocelectomy. The purpose of this retrospective study is to determine the frequency of scrotal pain following varicocelectomy.
Keywords: Varicocelectomy, retrospective study, scrotal pain, lump, surgery.